The Concept of Tri Guna in Strengthening Character Education Based on Hindu Sacred Teachings in the Modernization Era - Putera, Gusti Ngurah Ketut; Handoko, Handoko; Dharmawan, I Gusti Agung; Sana, I Nyoman Lingga; Gunada, I Wayan Agus (Jurnal Penelitian Agama Hindu, 2025)
The era of modernization presents significant challenges to ethical values and character, emphasizing the urgency of strengthening character education. Hindu philosophy, particularly the concept of Tri Guna, offers a relevant framework to address these challenges. This research aims to thoroughly analyze the relevance and potential application of the Tri Guna values (Sattwa, Rajas, Tamas) as a philosophical foundation for strengthening Hindu character education in the midst of modernization. The research method employed is library research with a qualitative approach, analyzing various primary and secondary literature sources descriptively and interpretatively. Research findings indicate that Tri Guna effectively maps the dynamics of basic human nature and provides guidance for character development. A balanced management of Sattwa (goodness/purity), Rajas (activity/passion), and Tamas (darkness/inertia) is identified as key to building integrity, moral resilience, and individual adaptability in facing the complexities of modern life. It is concluded that the Tri Guna concept holds strong relevance and strategic value as a basis for strengthening character education in the modern era, contributing to the formation of a generation with superior, balanced character capable of making positive contributions to society.